Internationalization and Global Tension: Lessons from History - Altbach, Philip G.; de Wit, Hans (International Higher Education, 2015)
Internationalization in higher education has always been linked to historical and political events. This article discusses how the dramatic events of the 20th century, such as the two world wars, and the Cold War, affected internationalization.